Kinetics of Oxidation of 3-Benzolypropionic Acid by N-Bromosuccinimide in Aqueous Acetic Acid Medium - Mohamed Farook, N.A. (Asian Journal of Chemistry, 2010)
The kinetics of oxidation of 3-benzoylpropionic acid (KA) by N-bromosuccinimide (NBS) have been studied in 50% acetic acid- 50% water (v/v) mixture. The reaction is fIrst order each in [NBS] and [KA]. A small increase in rate is observed with increase in [H+], A decrease in the dielectric constant of the medium at constant concentration of other reactants was found to be negligible on the rate of reaction. Variation in ionic strength of the medium and the addition of the reflection products (succinimide) has no signifIcant effect on the rates of reaction. From the kinetic data obtained, the activation parameters have been computed and a suitable mechanism has been proposed.